2022
DOI: 10.1080/11356405.2022.2102293
|View full text |Cite
|
Sign up to set email alerts
|

Unboxing micro-credentials: an inside, upside and downside view (Descifrando las microcredenciales: en qué consisten, ventajas e inconvenientes)

Abstract: Micro-credentials are the latest shiny new thing attracting the attention of politicians, policy-makers and educational leaders. This paper endeavours to ‘unbox’ the micro-credential by peeling away inherent tensions in competing definitions and underlying drivers. It reports the tripartite methodology adopted for a state-of-the-art literature review which offers an inside, upside and downside view on the micro-credential. Selected findings illustrate how the growth of the micro-credential needs to be understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…It is important to acknowledge that since the time this literature review was undertaken, several new publications have emerged, including other literature reviews (e.g., Brown et al, 2021;Brown and Mhichil, 2022;Fisher and Leder, 2022;McGreal et al, 2022;Nguyen et al, 2022). This work both confirms some of the findings of this study and introduces new developments in the micro-credentialing area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to acknowledge that since the time this literature review was undertaken, several new publications have emerged, including other literature reviews (e.g., Brown et al, 2021;Brown and Mhichil, 2022;Fisher and Leder, 2022;McGreal et al, 2022;Nguyen et al, 2022). This work both confirms some of the findings of this study and introduces new developments in the micro-credentialing area.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of micro-credentials is relatively new, formed by the joint efforts of researchers, practitioners, and policy makers. As noted by Brown and Mhichil (2022) the use of the definition mainly depends on "who is using the term and in what context." While most of the time definitions of microcredentials are based on a theoretical and scientific point of view, most of the existing models, prototypes, and practices are mainly explored and developed within the frameworks of different educational applied projects (e.g., MICROBOL, MICROHE).…”
Section: Theoretical Rationale For Micro-credentialsmentioning
confidence: 99%
“…Since both higher education institutions and private companies and organizations grant micro-credential certificates and these organizations do not act according to a common framework or determined standards, efforts have emerged to create a common framework for establishing the quality assurance procedures for micro-credentials. Brown et al (2021a) analyzed 149 publications on micro-credentials between 2015 and 2021. He found that 85.1% of the publications on micro-credentials were about higher education, 28.4% of them were Microcredentials and professional career about vocational education, 17.6% of them were about industry and institutions, 10.1% of them were about MOOCs, 1.4% of them were about community organizations and 5.4% of them were about K-12.…”
Section: Micro-credentialsmentioning
confidence: 99%
“…(8) Reducing education and training costs: Student debt is expressed as the second critical factor in the increase in the use of micro-credentials in the USA (Brown et al, 2021a(Brown et al, , 2021b.…”
Section: Microcredentials and Professional Careermentioning
confidence: 99%
See 1 more Smart Citation